2021
DOI: 10.3390/healthcare9050510
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Status of Italian Healthcare Workers during the First COVID-19 Pandemic Peak Period

Abstract: The pandemic of 2019 coronavirus disease (COVID-19) has burdened extraordinary psychological stress on the healthcare workforce. The present survey aimed to examine the personal resources and psychological symptoms associated with burnout in 933 healthcare workers in Italy during the COVID-19 outbreak period. Sociodemographic and occupational data, depression, anxiety, burnout, and post-traumatic symptoms, as well as psychological well-being, were cross-sectional assessed through an online questionnaire. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 84 publications
(94 reference statements)
3
28
0
2
Order By: Relevance
“…In Italy, Rossi et al [ 21 ] find that among 1,379 respondents (31.4% physicians, 77.2% women) surveyed in March 2020, the prevalence of depression (PHQ-9≥15) and anxiety (GAD-7≥15) was 24.7% (vs. 6.6% in our Italian sample) and 19.8% (vs. 9.5% in our Italian sample). Conti et al [ 34 , 35 ] find similar magnitudes. In the UK, Greenberg et al [ 36 ] find that among 709 staff (41% doctors) working in English hospitals in summer 2020, the prevalence of moderate (PHQ-9≥10) and severe (PHQ-9≥20) depression was 37% and 6%, respectively (26% and 6% among doctors, vs. 16.2% and 2.7% in our UK sample), and that the prevalence of moderate (GAD-7≥10) and severe (GAD-7≥15) anxiety was 27% and 11%, respectively (20% and 8% among doctors, vs. 14.2% and 5.9% in our UK sample).…”
Section: Discussionmentioning
confidence: 72%
“…In Italy, Rossi et al [ 21 ] find that among 1,379 respondents (31.4% physicians, 77.2% women) surveyed in March 2020, the prevalence of depression (PHQ-9≥15) and anxiety (GAD-7≥15) was 24.7% (vs. 6.6% in our Italian sample) and 19.8% (vs. 9.5% in our Italian sample). Conti et al [ 34 , 35 ] find similar magnitudes. In the UK, Greenberg et al [ 36 ] find that among 709 staff (41% doctors) working in English hospitals in summer 2020, the prevalence of moderate (PHQ-9≥10) and severe (PHQ-9≥20) depression was 37% and 6%, respectively (26% and 6% among doctors, vs. 16.2% and 2.7% in our UK sample), and that the prevalence of moderate (GAD-7≥10) and severe (GAD-7≥15) anxiety was 27% and 11%, respectively (20% and 8% among doctors, vs. 14.2% and 5.9% in our UK sample).…”
Section: Discussionmentioning
confidence: 72%
“…While the variation in prevalence may partly reflect the differences in COVID-19 burden in different regions and pandemic wave, a systematic review on burnout among physicians have indicated that the variability in prevalence estimates of burnout may also be attributed to variation in burnout definitions and assessment methods. 41 This is evident from the low prevalence of burnout reported by HCW working in high COVID-19 burden countries, including the study published by Conti, Fontanesi, 42 in which 26% of Italian HCW experienced burnout during the first COVID-19 pandemic peak period. Nevertheless, the findings published by Lu, Zhang 18 indicate that HCW working in public health settings may be more likely to experience burnout compared to HCW working in hospital settings, as 58% of public health service providers and 47.6% of clinical care providers were found to be burnout in their study.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted during the first COVID-19 pandemic peak period to analyze the burnout status of Italian HCWs [ 36 ] showed that a substantial part of the sample scored over the clinical levels of depression (57.9%), anxiety (65.2%), post-traumatic symptoms (55%), and also burnout (25.61%). The burnout variation highlighted in the study by Conti et al seemed to be independently affected by working on the front line, being doctors, experiencing reductions in mental health, as well as higher levels of post-traumatic stress disorder symptoms, in line with the results of our work.…”
Section: Discussionmentioning
confidence: 99%